Processes and Pathways of Family-School Partnerships Across Development - Sheridan, Susan M (Springer, 2015)
This book explores research on processes that influence family-school partnerships in support of student learning and education. It highlights research related to culture, contexts, and development as families and schools work together to promote smooth transitions and academic achievement. The volume discusses research related to family and community engagement with schools, and describes the various mechanisms by which partnerships may support students’ long-term developmental outcomes and success beyond school. Each chapter sets forth a forward-thinking research agenda aimed at further understanding and implementing the processes by which family-school partnerships promote children’s healthy adjustment.